SIKAP BAHASA PELAJAR DI KABUPATEN BANDUNG TERHADAP BAHASA INDONESIA SEBAGAI IDENTITAS NASIONAL BANGSA INDONESIA - Bulan, Deanty Rumandang; Radiansyah, Rifi Rivani; Hermawan , Dani (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2026)
This research is driven by the growing prominence of English, a trend that has emerged alongside rapid globalization, and it presents significant challenges for countries where English is not the primary language. This study investigates the language attitudes of students in Bandung Regency towards the Indonesian language, which serves as a vital component of national identity for Indonesian nation. Utilizing a qualitative approach, the research employed a questionnaire survey and written narrative inquiries to explore both social and linguistics perspectives of the respondents. Participants included high school students (SMA/SMK) from Bandung Regency area. The findings indicate that students exhibit a strong positive attitude towards the Indonesian language, perceiving it as a symbol of nationalism and a mean of fostering national unity. In general, this study confirms that Indonesian language remains a significant aspect of national identity, even amid the challenges posed by globalization and evolving language usage patterns among the youth.